Otroci na odru v Aarhusu 2017 - Ejgod Hansen, Louise (Amfiteater (Ljubljana), 2020)
In this article, the author discusses how the so-called participatory turn in culture has challenged the distinction between professional and amateur art and how we understand the value of the two. Building on and discussing Bentley's classical definition of theatre, she argues that the role of the producer and the recipient is changing and that the consequence is a more blurred distinction between artistic and social values and between process and product. By using examples from the European Capital of Culture Aarhus 2017 as cases, the author looks further into how culture for and culture with children have been combined and what the values and assumptions are behind such practices.
Keywords: 2017; Aarhus; amateur theatre; children's culture; European Capitals of Culture; evropska prestolnica kulture; ljubiteljsko gledališče; otroška kultura; participacija; participation; poklicno gledališče; professional theatre